Morphological and molecular identification of some indigenous fruit fly species in Sennar State - E.G., Abdelaziz; Virgilio, Massimiliano; De Meyer, Marc; H. H. Bashir, Nabil; E. Elkashif, Mohamed; O.H. Assad, Yousif (المجلة الزراعية; مجلد 10 عدد 1 (2012), 2022)
Fruit flies (Diptera:Tephritidae) are among the major constrains in commercial horticultural production in many African countries. DNA barcoding was used in this study to obtain quick and precise identification and to confirm the morphological identification of fruit fly specimens. Yellow sticky and Dome traps were used to collect some specimens from Sennar State whereas other specimens were reared under laboratory conditions at University of Gezira, from infested fruits. DNA from different specimens was extracted using the NucleoSpin® Tissue method. Three DNA fragments with sizes of 340, 220 and 280 bp. (base pairs) were recognized using specific primers and amplified from the 5’ region of the cox1 gene from the mitochondrial DNA to give a full barcode of 660 bp. Then, purified PCR products were subjected to sequencing reactions using the BigDye Cycle Sequencing Kit. The nucleotide sequences were aligned using the cluster W algorithm included in the Bioedit 7.0 software package. Sequence divergences were determined using similarity index (P-distance model). Morphologically, six fruit fly species, namely B. invadens , B. cucurbitae , C. cosyra , C. quinaria , D. ciliatus and D. longistylus were identified. The molecular phylo-genetic tree of the Sudanese fruit flies was established by sequencing of 12 specimens representing five fruit fly species at the mitochondrial cytochrome oxidase cox1 gene fragments. The morphological identification of the fruit fly specimens was confirmed by molecular identification. Although B. invadens is a highly variable species, specimens of the same species collected using yellow sticky traps, methyl eugenol and those reared from magad fruits (wild plant belonging  to the family Cucurbitaceae ) appeared to have the same or with a little variation (0.7%) in the DNA sequences cox1 fragments. D. ciliatus and B. cucurbitae appeared in separate clusters, with no variation among sequences of their specimens. The three common fruit fly genera: Bactrocera , Ceratitis and Dacus exhibited low intra-specific variation compared with that between inter-species in the amplified sequences.    تعتبر ذبابة الفاكهة (Diptera : Tephritidae)  من أهم الآفات التي تعيق الإنتاج  البستاني التجارى في عدد من الدول الأفريقية. أستخدمت تقنية التحليل الجزيئي (DNA barcoding) للحصول على تصنيف سريع ودقيق لأنواع ذبابة الفاكهة ولتأكيد التصنيف عن طريق الشكل الظاهري (مورفولولجي) لهذه الانواع.  أستخدمت  المصائد الصفراء اللاصقة والمصائد المقببة لجمع الحشرات الكاملة لذبابة الفاكهة من ولاية سنار، السودان، إضافة إلى تلك  التي رُبيت من اليرقات تحت الظروف المعملية بجامعة الجزيرة. أستخلص الـDNA من الحشرات الكاملة لذبابة الفاكهة باستخدام طريقة  NucleoSpin® Tissue. ثلاثة قطع بحجم 340، 220 و 280 زوج قاعدي قد تم التعرف عليها  وإكثارها من المنطقة الخامسة للجين Cox1 من DNA الميتوكوندريا لتعطي هذه القطع شريطاً من الـDNA بحجم 660 زوج قاعديٍ، استخدم في هذه العملية ثلاثة أزواج من البادئات المصممة خصيصاً لهذا الغرض. اجريت تفاعلات التسلسل النيوكليوتيدى لنواتج الـPCR المنقاة  باستخدام طريقة الـBig Dye Cycle sequencing kit .  اجرى التسلسل الخطى للنيوكليوتيدات باستخدام cluster W algorithm  المضمن فى ال Bioedit 7.0 software package. خلال هذه الدراسة ستة أنواع من ذبابة الفاكهة هي B. invadens, B. cucurbitae, C. cosyra, C. quinaria, D. ciliatus and D. longistylus   تم تصنيفها عن طريق الشكل الظاهري. تم استخدام نتائج التحليل الجزيئ للأنواع الحشرية في تصميم شجرة التشابهه (Phylogenetic tree)  والتي وضحت درجة التقارب بين أنواع ذبابة الفاكهة الموجودة في السودان، أيضاً تم تحديد التسلسل  النيوكلوتيدى لـ12 عينة حشرية تمثل خمسة أنواع من ذبابة الفاكهة، هذا التسلسل تمت مقارنته مع قواعد للبيانات وأعطى نتائج مماثلة للتصنيف عن طريق الشكل الظاهري. رغماً أن النوع B. invadens أظهر تبايناً في الشكل الظاهري إلا أن عينات النوع التي جمعت بإستخدام المصائد الصفراء اللاصقة والمصائد المقببة وتلك التي رُبيت من نبات المقد (نبات بري يتبع لعائلة القرعيات) قد أظهر إختلافاً صغيراً تراوح بين 0- 0.7% على مستوى تسلسل القواعد النتروجينية. عينات النوعين  D. ciliatus و B.cucurbitae ظهرا في عنقودين  (two clusters) مع عدم وجود اختلافات في تسلسل القواعد النتروجينة  لعيناتهما. أجناس ذبابة الفاكهة الثلاثة الأكثر شيوعاً Bactrocera, Ceratitis   و Dacus أظهرت تبايناً أقل في تسلسل القواعد النتروجينية داخل النوع عن ذلك الذي بين الأنواع.